Entrepreneurial Strategies: Theoretical and Practical Review (Journal - Entrepreneurial Strategies) - Soni Gustika (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study presents a comprehensive review of entrepreneurial strategies relevant to micro, small, and medium enterprises (MSMEs) as well as start-ups during the 2015–2025 period. The article discusses strategic entrepreneurship frameworks, the comparison of entrepreneurial decision-making logics (effectuation vs. causation), marketing strategies and digitalization, access to financing, growth and scaling strategies, as well as policy implications. In addition, several brief case studies and practical recommendations are provided that can be adopted by entrepreneurs and policymakers.